Determinan Indeks Pembangunan Manusia Di Provinsi Sulawesi Selatan Periode 2011-2020 - Tri Aprian Yudhistira; Jeffri Orlando Napitupulu; Nurul Aisyah Nst; Asnidar Asnidar; Ahmad Ridha (Pandawa : Pusat Publikasi Hasil Pengabdian Masyarakat, 2024)
Sulawesi Province has 7 districts/cities with a Human Development Index level that is not much different from the national Human Development Index, several districts/cities in Sulawesi Province have a Human Development Index below the national Human Development Index. The aim of this research is to analyze the Human Development Index and the factors that influence it in the South Sulawesi region for the 2011-2020 period. This research is quantitative research. The variables used in this research are the Human Development Index, Economic Growth, Poverty Level, and Gini Index. The panel data method is used for analysis in the form of cross data from 7 districts/cities in the South Sulawesi region and time series data for 2011-2020. The results of this research show that Economic Growth has a negative and significant effect on the Human Development Index, Poverty Level has a positive and insignificant effect on the Human Development Index, and the Gini Index has a positive and significant effect on the Human Development Index in the South Sulawesi region for the 2011-2020 period.